Confronting the Challenge of Continuous Professional Development for Physical Education Teacher Educators. Issue 1 (2nd January 2020) - Ward, Phillip; van der Mars, Hans
Abstract : The purpose of writing this article is to draw attention to the practice of physical education teacher education. The hope is to engage in an ongoing conversation with teacher educators about promoting personal continuous professional development. Similar to P-12 physical educators, and those who prepare future physical education teacher educators, physical education teacher educators have a responsibility to engage in Continuous Professional Development (CPD). Professional development (PD) should be viewed as an active process in the sense that it is proactive and ongoing, it will produce outcomes, but it is not a destination. SHAPE America as the field's national organization, has a responsibility to provide PD opportunities for teacher educators through its various activities.